Ideological State Apparatuses and Its Oppositions in Matt Reeves’ Film The Batman - Zhafirah, Muthiah Qalbu; Napitupulu, Johanes Claudio Perdana; Pasopati, Rommel Utungga; Hariyono, Hariyono; Kartiningsih, Rindrah (ELite Journal : International Journal of Education, Language and Literature, 2025)
This article describes how the article tries to explore the Ideological State Apparatuses (ISAs) and its oppositions in Matt Reeves’ Film The Batman. The film of The Batman, directed by Matt Reeves, is a 2022 superhero film based on the DC Comics character, Batman. The writers of this article employ a qualitative method, which allows the reader to learn more about the object's background. This movie has deep ideological themes, especially when it comes to Althusser's ideology theory, which underlines how the movie shows the complicated connection between justice, class, and power. The analysis looks at how different political issues are involved since it could demonstrate actions taken by the power structure against those under them. In conclusion, The Batman not only explores such superhero aspect in a film, but also how the characters must face various dominations by opposing such ISAs.